Developing your teaching style: increasing effectiveness in healthcare teaching. Issue 977 (7th March 2007) - Mohanna, Kay; Chambers, Ruth; Wall, David
Abstract : This paper reports the first stage in the development of a tool, the Six Staffordshire Teaching Styles Questionnaire, designed to raise awareness in teachers about their teaching style. Effective teachers are adaptable and flexible in providing variety in their teaching activities, aiming to match their manipulation of the teaching and learning environment to the needs of the learner, but teachers should also know what type of activities they are most effective at delivering. Just as mismatched learning styles can cause dysfunctional learning situations, one of the causes of stress in teachers can be an incongruency between the type of activities they believe are effective, or feel they are good at carrying out, and external expectations of "good teaching".